EVALUATING KERALA’S COMMITMENT TO RESPONSIBLE TOURISM: INSIGHTS FROM DOMESTIC TOURISTS - Baral, Ankit; Rahman, Faslu; Ariyaputhiri, Sadanandam (Palash: A Journal of Hospitality and Tourism Service Management, 2025)
Kerala, renowned as ‘God’s Own Country,’ has emerged as a leader in India’s responsible tourism sector, attracting 21.8 million domestic tourists in 2023 through its unique offerings in cultural, wellness, and rural tourism experiences. This study examines domestic tourists’ perceptions of Kerala’s responsible tourism initiatives, with four specific objectives: (1) To analyze socio-economic and tripographic profiles of visitors, (2) To assess how demographic factors influence satisfaction levels, (3) To evaluate the alignment between expectations and actual experiences, and (4) To identify critical gaps in responsible tourism offerings. Using a quantitative approach, data was collected through a structured questionnaire administered to domestic tourists, incorporating both tripographic details and Likert-scale responses. The analysis employed descriptive statistics, paired sample t-tests, and one-way ANOVA to process the survey results. Findings reveal that while tourists show overall satisfaction with cultural and festival tourism (with 78% expressing revisit intention), significant expectation satisfaction gaps exist in wellness tourism (particularly Ayurveda services) and rural infrastructure. The study highlights the need for standardized service quality and enhanced rural connectivity to strengthen Kerala’s position as a sustainable tourism destination, offering actionable insights for policymakers and industry stakeholders to optimize the state’s responsible tourism framework